CHARACTERISTICS OF PATIENTS WITH PANIC DISORDERS P THERE IS HYPERTHYROIDISM ACCOMPANIED BY TONSIL HYPERTROPHY AND THYROID EYE DISEASE WITH ECG PICTURE SICK DYSFUNCTION NODE - R. Mohamad Javier 1*, Satrio Wicaksono 2, Basyar Adnani 3, Nabila Ramadina 4, Kelvin Florentino Kaisar 5, Moh Iqbal Setiawan 6, Arief Dewantara 7, Asti Yumna Adiningrum 8, Vania Putri Salsabilla 9, Budi Prakoso 10, Pertiwi Febriana Chandrawati 11; Subandono Bambang Indrasto 12 (Chelonian Research Foundation, 2024)
Background: Hyperthyroidism is an endocrine disorder with the second highest incidence rate after diabetes, and Graves' disease is the most common cause of hyperthyroidism. Objective: To determine the characteristics of patients with panic disorder in hyperthyroidism with an ECG picture of sick node dysfunction. Methods: This study is a Systematic Review using the Preferred Reporting Items for Systematic Reviews and Meta-analysis or com method. This method is carried out systematically following the correct stages or research protocols. The source was taken from the PubMed site, and the Google Scholar site with journals published in 201 7-2022 and then filtered the results as many as 15,486. Results: Journal clustering was carried out and obtained the number of journals indexed in Scopus Q1 as many as 2 journals, Q2 as many as 2 journals, indexed Sinta S1 as many as 1 journal, so that there were 5 extracted journals. Conclusion: The majority of journals discuss age and lifestyle associated with the characteristics of panic disorder, as well as the factors of hyperthyroidism determined by age, and hyperthyroidism associated with panic disorder, ECG picture of sick node dysfunction. Keywords: Characteristics Patients, Hyperthyroid, Panic disorders, Sick Nodus Dysfunction, Hyperthyroidism.